2023
DOI: 10.55976/rppe.1202321285-20
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for the transition from preschool to primary school education in an online environment

Zoi T. Apostolou

Abstract: The Covid-19 world health crisis has profound implications and its consequences throughout the world have social, cultural, economic and educational ramifications. Worldwide, preschool teachers were forced to develop the students' learning experience in a new online environment. This research aims to investigate preschool teachers' views about literacy and literacy practices during face-to-face and remote teaching. As a result, the effectiveness of these practices during remote teaching to support the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…The issue of Internet accessibility and the lack of technical means that would allow children to participate in ERT has been consistently reported in the Greek context (e.g. Markaki & Kostas, 2022;Gkoros & Papageorgiou, 2023;Apostolou, 2023). Similar findings from other countries also indicate that a number of preschool children could not attend remote teaching due to a lack of resources (e.g.…”
Section: Preschool Education In Greece During the Covid-19 Pandemicmentioning
confidence: 56%
See 4 more Smart Citations
“…The issue of Internet accessibility and the lack of technical means that would allow children to participate in ERT has been consistently reported in the Greek context (e.g. Markaki & Kostas, 2022;Gkoros & Papageorgiou, 2023;Apostolou, 2023). Similar findings from other countries also indicate that a number of preschool children could not attend remote teaching due to a lack of resources (e.g.…”
Section: Preschool Education In Greece During the Covid-19 Pandemicmentioning
confidence: 56%
“…While not the case with all teachers, two participants reported that many children were unable to participate in remote education due to lacking the necessary technological equipment (e.g. Yıldırım, 2021; Timmons et al, 2021;Nikolopoulou, 2022;Markaki & Kostas, 2022;Gkoros & Papageorgiou, 2023;Apostolou, 2023), which indicated that they were practically excluded from the education system. This practice could be detrimental to children's sense of belonging to school, as it resonates with exclusion and rejection and denies children the opportunity to participate in education and develop socialemotional and academic skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations